Creating Shared Value Through National Dental Health Month as a Corporate Social Responsibility - Annastasya Meisa Putri; Andreo Wahyudi Atmoko (Journal of Social Research, 2025)
This study aims to analyze PT Unilever Indonesia's social responsibility (CSR) strategy. The sample from this study is Pepsodent through the National Dental Activity Month (BKGN) activity. The method used in this study is a literature study by analyzing previous journal articles and company reports. The results of the analysis show that Pepsodent's CSR program through National Dental Health Month can create shared value for society and businesses by improving stakeholder relationships, promoting long-term benefits for businesses, and improving business reputation. This program can also increase public awareness about dental and oral health, as well as help restore dental and oral care habits. However, the expansion of the scope of this program area still needs to be done to other cities and remote areas in Indonesia so that it can increase the effectiveness of this CSR program in creating shared value for the community and businesses.